MODIFIKASI DAN UJI KINERJA ALAT PENANAM KEDELAI TIPE ROLLING INJECTOR PLANTER - , R.M PASCHA ADI S, Dr.Ir. Bambang Purwantana, M.Agr. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
It is very crucially needed to increase the quality of rolling injector planter tool of soybean modified compared with the conventional one. The aim of the research is to modify the planting tool of the rolling injector type, primarily the modification of the opening heel and the basin of the intercepting seed. It is also meant to increase the lack of previous modification. This research is expected to check the function of that tool as the planting seed and to compare the work system of the previous tool in the field. The research is done by identifying the lack of the conventional tool. It is also hoped to design that tool by increasing the interception basin and the opening heel. That tool is treated in the three types of soil: entirely soft, medium, and hard soil. The data collected are in the form of the number of empty hole, the distance of the empty hole-seed and broken seed, and the broken seed, the depth of the hole, the distance of the hole, and the length of the planting time. That is also purposed to determine the percentage number of the planting time, the hole, the scattered seed, and the broken seed, the length of the hole, the average of soil distance, and the certainty of that work tool on the three types of soil. The results show that the modified rolling injector planter (1) can reduce the seed dibbled the number of the empty hole, and the percentage of the broken seed, (2) can increase the work capacities which consist of 1) the highest work capacity toward the soft soil, 2) the highest planting time toward the hard soil, 3) the depth of the plant toward the soft soil, 4) the percentage numbers of the highest broken seed toward the hard soil, the highest scattered soil toward the soft soil, and the highest empty hole toward the soft soil. Therefore, since the F counting value is higher than the F table, it can be concluded that the variation types of the rough soil toward the soft, medium, and hard soil in this research influence the similar spreading seed on the application of rolling injector planter.